2007
DOI: 10.1212/01.wnl.0000277457.17420.b5
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and significance of anti-natalizumab antibodies

Abstract: The incidence of persistent antibody positivity associated with natalizumab is 6%. Reduced clinical efficacy is apparent in persistently positive patients. Patients with a suboptimal clinical response or persistent infusion-related adverse events should be considered for antibody testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
242
5
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(262 citation statements)
references
References 12 publications
9
242
5
6
Order By: Relevance
“…This has been shown to happen with abciximab 178 and natalizumab 179 . In the case of abciximab, this can also lead to severe thrombocytopenia, although this is not solely due to anti-abciximab antibodies as it also occurs with small molecule α IIb β 3 antagonists 178 .…”
Section: Discussionmentioning
confidence: 97%
“…This has been shown to happen with abciximab 178 and natalizumab 179 . In the case of abciximab, this can also lead to severe thrombocytopenia, although this is not solely due to anti-abciximab antibodies as it also occurs with small molecule α IIb β 3 antagonists 178 .…”
Section: Discussionmentioning
confidence: 97%
“…Nonetheless, there are examples that are widely, if not universally, employed. Neutralising antibody levels for IFN 34 and for natalizumab 35 explain a proportion of poorer efficacy of these medications. More generally, T2 lesion increases and brain volume reduction on treatment are predictive of longer term clinical efficacy, at least at a group level.…”
Section: Personalised Medicine For Multiple Sclerosis: Is It Needed?mentioning
confidence: 99%
“…In another phase II singledose trial, O'Connor et al [2004] could not observe such a rebound effect. Although neutralizing antibodies decreased the clinical and MRI benefit of natalizumab, there was no rebound phenomenon in the pivotal phase III trials [Calabresi et al 2007]. Vellinga et al [2008] found that lesion activity increased after cessation of treatment and almost only in patients who received up to eight infusions.…”
Section: Natalizumab Treatment Guidelinesmentioning
confidence: 99%
“…In patients with persistent anti-natalizumab antibodies the level of natalizumab remains below the limit of quantification. Owing to high therapy costs and near loss of efficacy in persistently antibodypositive individuals [Calabresi et al 2007], antibody testing is justified in every patient receiving natalizumab. The antibody testing should be repeated after 2-3 months.…”
Section: Anti-natalizumab Antibodiesmentioning
confidence: 99%